2016
DOI: 10.1590/1807-1929/agriambi.v20n2p138-143
|View full text |Cite
|
Sign up to set email alerts
|

Silicon fertilization and soil water tensions on rice development and yield

Abstract: A B S T R A C TThe cultivation of upland rice (Oryza sativa) in Brazil occurs mainly in the Cerrado, a region with adverse weather conditions. The use of silicon in its cultivation becomes important, since this nutrient provides higher rigidity, lower transpiration and higher resistance to dry spells in rice plants. The objective of the present study was to evaluate the effect of silicon fertilization and soil water tensions on upland rice development and yield in a Cerrado Oxisol. A 5 x 5 fractionated factori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
3
0
1
Order By: Relevance
“…Although DE OLIVEIRA et al (2016) found negative effects of silicon on the profiling and on the number of panicles in rice plants, possibly due to the higher absorption of silicon and lower absorption of phosphorus and nitrogen, favored by chemical similarity (460 and 490 mg dm -3 Si), there may have been higher absorption of silicon and less absorption of these two elements, which are essential for lamination and panicle formation. This subject is worthy of further study at the soil chemistry level.…”
Section: Inovagri International Meeting 2017mentioning
confidence: 89%
“…Although DE OLIVEIRA et al (2016) found negative effects of silicon on the profiling and on the number of panicles in rice plants, possibly due to the higher absorption of silicon and lower absorption of phosphorus and nitrogen, favored by chemical similarity (460 and 490 mg dm -3 Si), there may have been higher absorption of silicon and less absorption of these two elements, which are essential for lamination and panicle formation. This subject is worthy of further study at the soil chemistry level.…”
Section: Inovagri International Meeting 2017mentioning
confidence: 89%
“…Generally, continued water deficit conditions until the reproductive stage may result in a loss of physiological activity and water absorption, which may have severe consequences on rice yield formation. Increased soil water deficit from 0 to −60 kPa reduced grain numbers and seed setting rate (higher sterility percentage) in rice (Oliveira et al, 2016). Thus, variations in water regimes at anthesis and/or grain filling stages possibly reduced the filled grain %, 1000‐grain weight, and yield in rice.…”
Section: Discussionmentioning
confidence: 99%
“…Also, Silicon can enhance antioxidant defense and then decrease oxidative stress in plants under drought, and it can increase the photosynthesis and relevant carboxylase activities, as found in wheat by Gong and Chen, (2012). Also, Pilon et al (2013) found that silicon application increased leaf area and chlorophyll concentration of well-watered potato plants, improved plant growth parameters and pigment concentration of wheat, (Maghsoudi et al (2015) and rice Oliveira et al (2016). 3.3.…”
Section: Survival % Of Sweet Potato Vines After 15 Days From Plantingmentioning
confidence: 97%